Morocco Economic Monitor, Fall 2020 : From Relief to Recovery - World Bank (World Bank, Washington, DC, 2021)
he COVID-19 pandemic has abruptly interrupted more than two decades of sustained socio-economic progress in Morocco. In 2020 the country will suffer its first recession since mid-1990s, and the economic contraction registered in the second quarter (broadly coinciding with the confinement) is the largest on record. This is the result of the combined supply, demand and external shocks triggered by the pandemic, but also of the effects of adverse weather conditions on agricultural output. The crisis is having a severe impact on jobs and household incomes, generating a spike in unemployment and a deterioration of poverty and vulnerability indicators. Although the Moroccan economy exhibits some signs of recovery, the situation remains fragile given that epidemiological trends are worse now than they were during the first wave of contagions.